Prosodic correlates of subclausal quotation marks - Kasimir, Elke (ZAS Papers in Linguistics, 2008)
We present the results of an experimental study which targets prosodic correlates of subclausal quotation marks. We found that written sentences containing passages enclosed by quotation marks were read aloud in a manner that significantly differs in prosody from spoken realizations of corresponding disquoted counterparts. However, we also observed that such prosodic marking of subclausal quotation wasn't strong enough to survive subsequent back-translation into written language: there was no correlation between the presence/absence of quotation marks in the original written examples, and the presence/absence of quotation marks in corresponding back-translations from oral renditions. We investigated three different kinds of uses of quotation marks and found no systematic difference between them with respect to prosodic marking.